Steroidogenic, Metabolic, and Immunological Markers in Dairy Cows Diagnosed With Cystic Ovarian Follicles at Early and Mid-Late Lactation - Lima, Fabio S.; Acosta, Diego A. V.; Egan, Tonja R.; Skenandore, Cassandra; Sulzberger, Saige; French, Dennis D.; Cardoso, Felipe C. (Frontiers in Veterinary Science, 2019)
The etiology of cystic ovarian follicles (COF) remains a conundrum with steroidogenic, immunological, and metabolic dysfunctions linked to its development. Studies suggest that COF development may occur as a result of disruption of the insulin signaling pathway and the severity of a negative energy balance in dairy cows, but mid to late lactation cows diagnosed with COF are unlikely to have issues with energy metabolism. Herein, we characterized the mRNA expression of steroidogenic (LHCGR, StAR, CYP11A1, 3β-HSD, CYP19A), immunological (IL-1β, IL-6, IL-8, TLR-4, TNF), and metabolic markers (IGF-1, IRS1) in follicular fluid; and plasma and follicular fluid levels of E2, IL-1β, glucose, and NEFA in early and mid-late lactation COF cows. Lactating dairy cows were diagnosed as having COF (n = 11, follicle >20 mm persistent for 7 days, absence of corpus luteum, and flaccid uterus) while 11 herdmates cycling with a dominant follicle were classified as the control cows. Cows diagnosed with COF were classified as early lactation (COF-E, n = 5) cows, <35 days in milk (DIM); or mid-late lactation (COF-M/L, n = 6), ≥118 DIM cows. Results revealed that mRNA expression StAR was greater (P < 0.01) in COF-E cows than COF-M/L cows and the control cows. The mRNA expression CYP19A1 was lower (P < 0.01) in COF-E cows and COF-M/L cows than in the control cows. The mRNA expression IL-6 and IRS-1 tended to be greater and lower, respectively, in COF-M/L cows compared to the control cows. The mRNA expression IGF-1 was greater (P < 0.01) in COF-E and COF-M/L cows than in the control cows. The plasma and follicular fluid concentration of NEFA was greater (P < 0.05) in COF-E cows than in COF-M/L and the control cows. Cows with COF-E had disturbances in steroidogenic and metabolic markers, while cows with COF-M/L had steroidogenic, immunological, and metabolic dysregulations, suggesting that COF pathogenesis may vary between early and mid-late lactation dairy cows.